Modelagem bidimensional de hidrofobicidade e superhidrofobicidade em superfícies de pilares - Oliveira, Luciana Renata de (2010)
In this work we investigate the use of the Potts Cellular Model in simulations of the water droplets on flat hydrophobic and pillarlike surfaces surrounded by gas. Eight tests were chosen to validate the model, based on experimental and theoretical results: (1) the measurement of the contact angle on a flat hydrophobic surface; (2) the transition from Cassie to Wenzel states; (3) the measurement of the contact angle on the pillar-like structured surface in Wenzel and Cassie states; (4) the dependence of the contact angle on the roughness of the surface; (5) the measurement of the contact angle hysteresis; (6) the difference in angle hysteresis between Wenzel and Cassie states (7) the sliding of a droplet on inclined surfaces; and (8) the relationship between angle hysteresis and the velocity of the droplets on inclined surfaces. Our results are agree with the experimental and theoretical results suggesting that the Cellular Potts Model can be used as a tool in the theoretical studies these systems.